2014
DOI: 10.1128/mbio.00074-14
|View full text |Cite|
|
Sign up to set email alerts
|

Noncanonical MicroRNA (miRNA) Biogenesis Gives Rise to Retroviral Mimics of Lymphoproliferative and Immunosuppressive Host miRNAs

Abstract: MicroRNAs (miRNAs) play regulatory roles in diverse processes in both eukaryotic hosts and their viruses, yet fundamental questions remain about which viruses code for miRNAs and the functions that they serve. Simian foamy viruses (SFVs) of Old World monkeys and apes can zoonotically infect humans and, by ill-defined mechanisms, take up lifelong infections in their hosts. Here, we report that SFVs encode multiple miRNAs via a noncanonical mode of biogenesis. The primary SFV miRNA transcripts (pri-miRNAs) are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
102
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(112 citation statements)
references
References 52 publications
7
102
1
2
Order By: Relevance
“…1A). As expected, miR-132, which has previously been shown to inhibit IFN signaling (35,36) scored in our assay by reducing the IFN-induced transcription of the firefly-Luc reporter by 35%. Additionally, three herpesviral miRNAs consistently scored as having a ≥25% reduction (Fig.…”
Section: Significancesupporting
confidence: 82%
See 1 more Smart Citation
“…1A). As expected, miR-132, which has previously been shown to inhibit IFN signaling (35,36) scored in our assay by reducing the IFN-induced transcription of the firefly-Luc reporter by 35%. Additionally, three herpesviral miRNAs consistently scored as having a ≥25% reduction (Fig.…”
Section: Significancesupporting
confidence: 82%
“…S1). We chose to screen for miRNA-mediated inhibition of IFN as a potential widespread activity of viruses for two reasons: (i) proteins that hinder the IFN response are nearly universal among mammalian viruses, and (ii) we have already demonstrated that the unrelated viruses, Torque teno virus tth8 (TTV-tth8) and Simian Foamy virus of African green monkey (SFVagm) encode miRNAs that inhibit type I IFN signaling (34,35). Thus, we conducted a screen to identify those human viral miRNAs that block IFNmediated signaling.…”
Section: Significancementioning
confidence: 99%
“…Similarly, one viral miRNA produced by B-lymphotropic BLV, BLV-miR-B4, shares its seed sequence with host B-cell tumorigenic miR-29a (55). All of these viral miRNA mimics target the same set of genes as their host counterparts (54,55).…”
Section: The Boostermentioning
confidence: 99%
“…SFV of African green monkeys (SFVagm) produces at least 6 mature miRNAs from its long terminal repeat (LTR) regions by RNA polymerase III transcription (54). Two of these viral miRNAsSFVagm-miR-S4-3p and SFVagm-miR-S6-3p-exhibit seed sequence homology with host lymphoproliferative miR-155 and immunosuppressive miR-132, respectively (54). Similarly, one viral miRNA produced by B-lymphotropic BLV, BLV-miR-B4, shares its seed sequence with host B-cell tumorigenic miR-29a (55).…”
Section: The Boostermentioning
confidence: 99%
“…However, a few viruses generate miRNAs using unconventional mechanisms and proteins, such as RNAP III, tRNase Z, and the integrator complex (Pfeffer et al 2005;Bogerd et al 2010;Diebel et al 2010;Cazalla et al 2011;Kincaid et al , 2014Burke et al 2014;Diebel et al 2014;Feldman et al 2014). Previous work from our laboratory and others has demonstrated that the miRNAs derived from the 5 ′ end of 5 ′ triphosphorylated miRNA precursors expressed by bovine leukemia virus (BLV) and human adenovirus (AdV) predominantly contain a 5 ′ monophosphate (Xu et al 2009;Burke et al 2014).…”
mentioning
confidence: 99%